Acute Respiratory Distress Syndrome after Treatment of Metastatic Prostate Cancer with Taxotere: A Case Report and Literature Review - Ali Raufi; Jennifer Dotson; Mohamad Khasawneh (Case Reports in Urology)
Prostate cancer is the most common cancer in men. Docetaxel is a common chemotherapeutic agent that has proven its efficacy in the treatment of patients with both castration sensitive and resistant metastatic prostate cancer. We report a case of acute respiratory distress syndrome (ARDS) in a patient with metastatic prostate cancer treated with docetaxel (Taxotere). ARDS is very rare but life threatening complication of docetaxel which requires aggressive supportive care and close monitoring. Better awareness and prompt diagnosis of this treatment related ARDS will improve the effectiveness and outcome of its management.